Bees Hope: Poetic Reflections on Theorising Hope in a More-Than-Human World - Wardell, Susan (New Zealand Sociology, 2024)
Theorising hope in the Anthropocene must take into account the agencies and social actors of the more-than-human world. Here I present a poem that employs a creative and speculative approach to the idea of beekeeping as an assemblage of hope. This emerges from several years of personal/autoethnographic and academic engagement in the topics of ecological distress and climate emotion, through which I also became interested in honeybees (Apis mellifera) as a mobile symbol of both hope and loss in global environmentalist discourse, amid rising rates of hobbyist beekeeping, both globally and here in Aotearoa New Zealand. The poem, and following reflection points, considers the degree to which hope is shared between different (human and non-human) social actors in the assemblage of beekeeping. It explores the ways hope might be temporalised, embodied, relational or political; recognising unequally distributed and shifting agencies, or stakes, in the futures, at a bodily level, both within the colony and between bees and beekeepers. This poetic exploration of the epistemologies and ontologies of hope, based on the overarching question “How human is hope?”, spurs a call for critical attention to new ways of both understanding and relating to non-human others, as potential kin and co-participants in world-making, amid uncertain futures.